An Analysis of the Digital Religiosity of Islamic Religious Education Students at IAIN Kerinci on Social Media - Fauziah Rahmi; Dodi Hendrika (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
This study aims to analyze the digital religiosity of Islamic Education (PAI) students on social media, including forms of religious expression, influencing factors, and the consistency between digital expression and real-life practices. This research employs a qualitative approach with a descriptive method. Data were collected through observation, questionnaires, and interviews with PAI students who actively use social media. The findings indicate that students actively express religious values through various forms of religious content, such as Qur’anic verses, hadith, and da’wah messages. However, inconsistencies were found between religious expressions on social media and actual practices in daily life. These behaviors are influenced by the digital environment, level of religious knowledge, and motivations for using social media. The study concludes that students’ digital religiosity tends to be symbolic; therefore, strengthening Islamic education based on digital ethics and literacy is necessary.